Respuesta :
Answer: (1, 9)
Step-by-step explanation:
-6x = 48 - 6y divide by -6 → x = -8 + y
Now, use substitution method by replacing "x" in the second equation with (-8 + y)
-4x = 50 - 6y
-4(-8 + y) = 50 - 6y
32 - 4y = 50 - 6y
32 + 2y = 50
2y = 18
y = 9
Now, substitute "y" with 9 in the first equation:
x = -8 + y
= -8 + (9)
= 1
Check:
-4x = 50 - 6y
-4(1) = 50 - 6(9)
-4 = 50 - 54
-4 = -4 [tex]\checkmark[/tex]
Answer (1, 9)
Step-by-step explanation:
-6x = 48 - 6y divide by -6 → x = -8 + y
Now, use substitution method by replacing "x" in the second equation with (-8 + y)
-4x = 50 - 6y
-4(-8 + y) = 50 - 6y
32 - 4y = 50 - 6y
32 + 2y = 50
2y = 18
y = 9
Now, substitute "y" with 9 in the first equation:
x = -8 + y
= -8 + (9)
= 1
Check:
-4x = 50 - 6y
-4(1) = 50 - 6(9)
-4 = 50 - 54
-4 = -4
Step-by-step explanation: